التصور الرشدي لطبيعة الحركة بين المادة والصورة (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
سأحاول في هذا البحث الكشف عن طبيعة التصور الرشدي لحدوث الحركة بين الموجودات في العالم ، وطالما أن الموجودات تتألف من مادة وصورة فإن الحركة تقوم على الاتحاد بين المادة والصورة حتى تحصل عملية التحوّل من القوة الكامنة في المادة عن طريق الفعل الموجود في الصورة، وهنا يأتي دور الفاعل "المحرك" الذي يحرك المادة للاتحاد بالصورة عن طريق الحركة . وبذلك فإن الحركة إنما هي بمثابة صيرورة جدلية بين المادة والصورة التي تؤلف طبيعة الموجودات في العالم ، وبذلك تظهر الحركة على أنها إخراج المادة إلى الصورة عن طريق القوة والفعل بواسطة الصيرورة الحركية بين الموجودات . ومن ثم فإن تصور الحركة عند ابن رشد يبرز أهمية المادة والصورة والقوة والفعل كعناصر أساسية لحدوث الحركة في الوجود ، والتي تحتاج إلى محرك ومتحرك " المادة والصورة والفعل والفاعل". In this research I'm going to expose Averroes maturity conception of legal movement to occur in the world and among the assets ; as long as the assets are composed of material and form , the movement depends on the union between material and form until you get to the process of trans formation of the power in herent in the material by the action in the form . And here comes the role of the actor which moves the material toward the union with form through movement , so the movement also serves as a process of the dialectic between the material and form that consist the nature of the assets in the world , and thus  show the the movement it is bringing out of  material to the form by the dialectic of power and action by becoming kinetic between assets . Thus , the conception of movement to Averroes highlights the important of form power and act as essential elements for the occurrence in existence . He stressed the vole of each element in the movement as well as the movement needs an actor and moving thing which are (material ,form, actor).